Human Rights Based Litigation in Promoting Disaster Preparedness - Chamdani, Muchammad Chanif; Husnayaini, Dhiya' Sholiha (Faculty of Law, Universitas Negeri Semarang, 2023)
Indonesia grapples with an elevated susceptibility to natural disasters, as highlighted by the 2018 Indonesian Disaster Risk Index (IRBI), placing all provinces within the medium to high risk spectrum. The resulting devastation, losses, and adverse effects are compounded by societal vulnerabilities and a lack of capacity to manage such crises. This study advocates for a human rights-based approach to disaster management, serving as a dual tool to instigate government accountability and empower communities to enhance their resilience. A pivotal focus lies on preparedness as an essential factor, aiming to cultivate capabilities for efficient emergency management and seamless transitions from immediate response to sustained recovery. Recognizing the potential of effective preparedness measures in significantly mitigating the impact of disasters, this paper employs a normative approach, incorporating statutory and court case analyses, to scrutinize the feasibility and challenges of litigation. The objective is to assess the government's adherence to preparedness requirements, leveraging legal avenues to ensure comprehensive disaster resilience. This research sheds light on the prospects and hurdles of utilizing litigation as a mechanism for prompting government action and fostering a culture of preparedness within the Indonesian context.